Insurgence, Retreat, Reinvention: US For-Profit Higher Education - Garrett, Richard (International Higher Education, 2022)
The story of for-profit higher education in twenty-first century America opens new chapters on the possibilities and limits of for-profit sectors in mature higher education systems. This article summarizes dramatic for-profit enrollment growth in America in the 2000s, followed by regulatory pushback, consumer souring, and marked decline. Four possible for-profit futures are outlined.